Primary care indicators for disease burden, monitoring and surveillance of COVID-19 in 31 European countries: Eurodata Study - Ares-Blanco, Sara; Guisado-Clavero, Marina; Del Rio, Lourdes Ramos; Larrondo, Ileana Gefaell; Fitzgerald, Louise; Murauskienė, Liubovė; López, Naldy Parodi; Perjés, Ábel; Petek, Davorina; Petrazzuoli, Ferdinando; Petricek, Goranka; Sattler, Martin; et al. (European journal of public health, 2024)
BACKGROUND: During the COVID-19 pandemic, the majority of patients received ambulatory treatment, highlighting the importance of primary health care (PHC). However, there is limited knowledge regarding PHC workload in Europe during this period. The utilization of COVID-19 PHC indicators could facilitate the efficient monitoring and coordination of the pandemic response. The objective of this study is to describe PHC indicators for disease surveillance and monitoring of COVID-19's impact in Europe. METHODS: Descriptive, cross-sectional study employing data obtained through a semi-structured ad hoc questionnaire, which was collectively agreed upon by all participants. The study encompasses PHC settings in 31 European countries from March 2020 to August 2021. Key-informants from each country answered the questionnaire. Main outcome: the identification of any indicator used to describe PHC COVID-19 activity. RESULTS: Out of the 31 countries surveyed, data on PHC information were obtained from 14. The principal indicators were: total number of cases within PHC (Belarus, Cyprus, Italy, Romania and Spain), number of follow-up cases (Croatia, Cyprus, Finland, Spain and Turkey), GP's COVID-19 tests referrals (Poland), proportion of COVID-19 cases among respiratory illnesses consultations (Norway and France), sick leaves issued by GPs (Romania and Spain) and examination and complementary tests (Cyprus). All COVID-19 cases were attended in PHC in Belarus and Italy. CONCLUSIONS: The COVID-19 pandemic exposes a crucial deficiency in preparedness for infectious diseases in European health systems highlighting the inconsistent recording of indicators within PHC organizations. PHC standardized indicators and public data accessibility are urgently needed, conforming the foundation for an effective European-level health services response framework against future pandemics.
Keywords: Cross-Sectional Studies; Cost of Illness; pandemie; COVID-19; osobní újma zaviněná nemocí; Pandemics; Humans; primární zdravotní péče; lidé; Kypr; Cyprus; průřezové studie; Primary Health Care